Assessing and Prioritizing Agricultural Drone Sprayers in Kerman Province: an Analytic Hierarchy Process (AHP) Approach - Zinat Eskandari Nasab; Hossein Maghsoudi (Biomechanism and Bioenergy Research)
Given the limited awareness among farmers regarding agricultural spraying drones, the Analytic Hierarchy Process (AHP) method serves as a valuable tool to assist farmers in systematically selecting the most high-performing drone from the available options. This research employed the AHP method, utilizing Expert Choice software, to evaluate and prioritize several drone sprayers in the southern region of Kerman province, specifically Pelikan1, T16, T20, and MG-1P. Various parameters, including coverage percentage, spraying quality coefficient, spraying uniformity, device price, amount of pesticide consumption, and droplet diameter, were thoroughly examined to establish distinct priorities for each parameter. Within the AHP framework, the coverage percentage was accorded the highest weight of 0.340, while spraying uniformity received the lowest weight of 0.100. The spraying quality coefficient, cost, and amount of pesticide consumption were assigned weights of 0.222, 0.185, and 0.153, respectively. Consequently, the T16 drone sprayer emerged with the highest rank, carrying a weight of 0.277 in comparison to other drone sprayers. In contrast, Pelikan1 attained the lowest rank with a weight of 0.225. The prioritization of spraying drones based on their performance is as follows: T16, T20, MG-1P, and Pelikan1, respectively. This study provides valuable insights for farmers seeking to optimize the utilization of drone sprayers in the southern region of Kerman province.